The mothers, Omega-3 and mental health study - Vazquez Delia; Berman Deborah; Hamilton Susan; Allbaugh Lucy; Keeton Kristie; Klemens Chelsea; Chilimigras Julie; Mozurkewich Ellen; Marcus Sheila; Djuric Zora; Vahratian Anjel (BMC, 2011)
Abstract Background Major depressive disorder (MDD) during pregnancy and postpartum depression are associated with significant maternal and neonatal morbidity. While antidepressants are readily used in pregnancy, studies have raised concerns regarding neurobehavioral outcomes in exposed infants. Omega-3 fatty acid supplementation, most frequently from fish oil, has emerged as a possible treatment or prevention strategy for MDD in non-pregnant individuals, and may have beneficial effects in pregnant women. Although published observational studies in the psychiatric literature suggest that maternal docosahexaenoic acid (DHA) deficiency may lead to the development of MDD in pregnancy and postpartum, there are more intervention trials suggesting clinical benefit for supplementation with eicosapentaenoic acid (EPA) in MDD. Methods/Design The Mothers, Omega-3 and Mental Health study is a double blind, placebo-controlled, randomized controlled trial to assess whether omega-3 fatty acid supplementation may prevent antenatal and postpartum depressive symptoms among pregnant women at risk for depression. We plan to recruit 126 pregnant women at less than 20 weeks gestation from prenatal clinics at two health systems in Ann Arbor, Michigan and the surrounding communities. We will follow them prospectively over the course of their pregnancies and up to 6 weeks postpartum. Enrolled participants will be randomized to one of three groups: a) EPA-rich fish oil supplement (1060 mg EPA plus 274 mg DHA) b) DHA-rich fish oil supplement (900 mg DHA plus 180 mg EPA; or c) a placebo. The primary outcome for this study is the Beck Depression Inventory (BDI) score at 6 weeks postpartum. We will need to randomize 126 women to have 80% power to detect a 50% reduction in participants' mean BDI scores with EPA or DHA supplementation compared with placebo. We will also gather information on secondary outcome measures which will include: omega-3 fatty acid concentrations in maternal plasma and cord blood, pro-inflammatory cytokine levels (IL-1β, IL-6, and TNF-α) in maternal and cord blood, need for and dosage of antidepressant medications, and obstetrical outcomes. Analyses will be by intent to treat. Discussion This study compares the relative effectiveness of DHA and EPA at preventing depressive symptoms among pregnant women at risk. Trial registration Clinical trial registration number: NCT00711971